Cross-talk between cardiac lymphatics and immune cells regulates inflammatory response and cardiac recovery after myocardial infarction - Yang, Zhihua; Zhang, Zeyu; Feng, Shaoling; Ning, Xujin; Guo, Liuli; Du, Yijia; Wang, Shuai; Wang, Xianliang; Mao, Jingyuan (Frontiers in Immunology, 2025)
Myocardial infarction (MI) is a life-threatening disease with high morbidity and mortality, closely associated with immune-inflammatory responses. As essential pathways for immune cell clearance and interstitial fluid drainage, lymphatic vessels are critical in regulating tissue fluid homeostasis and systemic immune surveillance. Cardiac lymphatics interact with immune cells, directly and indirectly, to mediate post-MI inflammation, participate in the clearance of necrotic tissue, and contribute to cardiac remodeling. Studies indicate that after MI, promoting cardiac lymphangiogenesis can accelerate the clearance of infiltrated immune cells, reduce the production of pro-inflammatory cytokines, improve myocardial edema, mitigate inflammatory responses and fibrosis, and support recovery of cardiac function. Meanwhile, immune cells regulate the structure and function of cardiac lymphatics, influencing lymphangiogenesis and drainage efficiency. The interaction between cardiac lymphatics and immune cells is crucial for myocardial repair post-MI. This review first systematically summarizes the structure and function of cardiac lymphatics, then sorting the relationship between cardiac lymphatics and immune cells and their roles in myocardial repair after MI and finally proposes therapeutic strategies targeting the interaction between cardiac lymphatics and immune cells in MI treatment, to provide prospective insights for the prevention and treatment of MI in the future.